2018
DOI: 10.3390/s18041210
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Fault Diagnosis of Rolling Bearings via Adaptive Projection Intrinsically Transformed Multivariate Empirical Mode Decomposition and High Order Singular Value Decomposition

Abstract: Rolling bearings are important components in rotary machinery systems. In the field of multi-fault diagnosis of rolling bearings, the vibration signal collected from single channels tends to miss some fault characteristic information. Using multiple sensors to collect signals at different locations on the machine to obtain multivariate signal can remedy this problem. The adverse effect of a power imbalance between the various channels is inevitable, and unfavorable for multivariate signal processing. As a usef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…Where, f (t), as shown in Formula (12), is a pollution-free signal. To avoid generality loss, n(t) is assumed as mixed Gaussian noise, which is a mixture of Gaussian signals with mean and variance of (0, 1), (2,5), (4,10). α is noise weight.…”
Section: Simulation Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Where, f (t), as shown in Formula (12), is a pollution-free signal. To avoid generality loss, n(t) is assumed as mixed Gaussian noise, which is a mixture of Gaussian signals with mean and variance of (0, 1), (2,5), (4,10). α is noise weight.…”
Section: Simulation Experimentsmentioning
confidence: 99%
“…pollution-free signal. To avoid generality loss, ( ) n t is assumed as mixed Gaussian noise, which is a mixture of Gaussian signals with mean and variance of (0, 1), (2,5), (4,10 Let us take =0.01  , signal-to-noise ratio SNR1 = 13.5392 as an example. The time domain waveforms of the three signals ( ) f t , ( ) n t  , ( ) y t are shown in Figure 5, and the frequency spectrum, i.e., frequency domain waveform, is shown in Figure 6.…”
Section: Simulation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy variation of the 3× component (where X represents the frequency corresponding to the rotating speed) extracted based on Wavelet Packet Transform [43][44][45] was used to quantify the crack depth of a crack with known crack location in a rotor by Gómez et al [46], and the analytical Jeffcott rotor model and the corresponding experimental rotor with a saw-cut crack were studied to validate the method. EMD method [47][48][49] was applied to steady-state responses generated from a Jeffcott rotor to extract the 3× and 2× components in the neighborhood of 1/3 and 1/2 of the critical rotating speed by Guo et al [50], results showed that the variation of averaged amplitudes of super-harmonic components provided clear and robust signatures of early cracks in rotating rotors. However, from the literature, few researches have been carried out to identify both the location and depth of a crack in a rotor with these super-harmonic features.…”
Section: Introductionmentioning
confidence: 99%
“…In the aspect of EMD, Abdelkader et al realized the early fault detection of rolling bearing based on the improved EMD method [8]. Yuan et al applied the EMD method to the multifault diagnosis of bearing [9]. Unfortunately, these popular methods also have unsolved problems: one is the selection of thresholds and wavelet basis in wavelet transform, and another one is the mode fixing and end effect in the EMD method [10].…”
Section: Introductionmentioning
confidence: 99%